(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
“Whatever the motives of those Indians who fought againsttheir own countrymen and in support of the foreigners they were not ‘traitors’as Savarkar has dubbed them, but the unconscious instruments of our moderndestiny : they were the indirect makers of modern India. Those who weredefeated looked backwards; those who were victories looked to the future.”